2020
DOI: 10.1186/s12911-020-1025-3
|View full text |Cite
|
Sign up to set email alerts
|

Tracking physical activity using smart phone apps: assessing the ability of a current app and systematically collecting patient recommendations for future development

Abstract: Background: Within the United Kingdom's National Health System (NHS), patients suffering from obesity may be provided with bariatric surgery. After receiving surgery many of these patients require further support to continue to lose more weight or to maintain a healthy weight. Remotely monitoring such patients' physical activity and other healthrelated variables could provide healthworkers with a more 'ecologically valid' picture of these patients' behaviours to then provide more personalised support. The curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…Overall, 11 different apps were tested, in which [ 15 , 19 , 28 , 32 , 37 , 42 ] studies were conducted using the My Jump and My Jump App 2, [ 17 , 18 , 27 , 30 , 34 , 38 , 44 , 46 ] the Powerlift, previously named Mylift, [ 36 ] the Ergo Arm Meter, [ 35 ] the Smartphone accelerometer, [ 33 , 41 ] the Speedclock App, [ 31 ] the MySprint App, [ 29 , 45 ] the ILoad, and [ 26 ] the Styrd App.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, 11 different apps were tested, in which [ 15 , 19 , 28 , 32 , 37 , 42 ] studies were conducted using the My Jump and My Jump App 2, [ 17 , 18 , 27 , 30 , 34 , 38 , 44 , 46 ] the Powerlift, previously named Mylift, [ 36 ] the Ergo Arm Meter, [ 35 ] the Smartphone accelerometer, [ 33 , 41 ] the Speedclock App, [ 31 ] the MySprint App, [ 29 , 45 ] the ILoad, and [ 26 ] the Styrd App.…”
Section: Resultsmentioning
confidence: 99%
“…Various parameters are measured by practitioners under physical conditions [ 3 , 34 ]. For example, it is used to measure balance [ 43 ], distance [ 44 ] and physical activity [ 45 ]. In addition, it has been reported in the research that the use of mobile applications increases the level of physical activity by increasing the level of physical fitness [ 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite all the above, there is a dearth of data on the effects of exercise on WL and WL maintenance after BS [14]. Although inclusion of PA and exercise in clinical follow-up schedules greatly benefits BS patients since this leads to greater improvements in body composition, bone mineral density, muscle strength, and fitness [19], participants' activity pre-and postsurgery showed that their PA levels pre-and post-surgery did not differ [20]. These findings suggest the need to measure PA post-BS and incorporate it in the analysis in order to realistically compare the effectiveness of various BS procedures.…”
Section: Resultsmentioning
confidence: 99%
“…The Bariatric Analysis and Reporting Outcome System (BAROS) and its modification [37,58] evaluate changes in quality of life, metabolic effects, and complications after BS, but do not consider the quality of diet or PA [21]. Recently, a study used a mobile phone App to track PA among patients considered for and who had previously undergone BS [20]. Total energy expenditure can be accurately evaluated using doubly labeled water, but it is less practical for large-scale research [59,60].…”
Section: Data On Post-op Pa and Diet Among Bariatric Patientsmentioning
confidence: 99%
“…However, anywhere delivery of the patient's data is not supported by those systems. Another similar previous study focuses on sensing and sending patients' data directly from PDA to the doctors [18], [19]. They propose the system, which is named "Remote Patient Monitoring" (RPM).…”
Section: Introductionmentioning
confidence: 99%